2001
DOI: 10.2307/4053198
|View full text |Cite
|
Sign up to set email alerts
|

Doctors and Patent Medicines in Modern Britain: Professionalism and Consumerism

Abstract: In the late nineteenth century professionalism and consumerism collided in a vociferous debate over the commodification of health. In medical journals, before government panels and through independent publications, doctors condemned “quackery,” especially patent medicines—the Victorian appellation for over-the-counter drugs. They dismissed myriad pills, tonics and appliances as addictive, dangerous, or useless. This professional critique, doctors claimed, was an altruistic defence of patients. Their commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Indeed, in the context of patent medicines, such vague references were often fake and relied on consumer trust in a brand to be honest and ethical. 52 Nonetheless, weight is added to Virol's testimonials by the accompanying images of smiling, healthy-looking babies, often with blonde hair and no clothes to signal their purity 53 , who are framed in such a way that they can be easily interpreted as the children referred to in the testimonials. Naked children were a common feature of Victorian and Edwardian advertising, used particularly during the 'pure foods' campaign against adulteration.…”
Section: 'Don't Let Your Child Die': Preventing Malnutrition With Virolmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the context of patent medicines, such vague references were often fake and relied on consumer trust in a brand to be honest and ethical. 52 Nonetheless, weight is added to Virol's testimonials by the accompanying images of smiling, healthy-looking babies, often with blonde hair and no clothes to signal their purity 53 , who are framed in such a way that they can be easily interpreted as the children referred to in the testimonials. Naked children were a common feature of Victorian and Edwardian advertising, used particularly during the 'pure foods' campaign against adulteration.…”
Section: 'Don't Let Your Child Die': Preventing Malnutrition With Virolmentioning
confidence: 99%
“…94 In other cases, advertisements make explicit references to doctors, giving the impression that the product has been medically approved. However, these references are deliberately vague, making it challenging to disprove (or indeed prove) them: 'The doctor is the best friend of Virolax'; 'the doctor knows that … '; 'the doctor informs that … ' Bartrip 95 and Loeb 96 have explored the use of doctor testimonials in patent medicine advertisements and have found that many were, in fact 'figments of the advertising imagination' extorted or taken out of context. The British Medical Journal even warned of this practice in a 1912 article, 97 advising consumers to be aware of endorsements by doctors whose names were not in the Medical Register, as well as 'vague titles' and 'misapplied quotes'.…”
Section: 'Don't Let Your Child Die': Preventing Malnutrition With Virolmentioning
confidence: 99%
“…12 George Fulford, who 'purchased Jackson's patent for the paltry sum of $53.01' in 1890, 13 reportedly amassed a fortune of over £1.6 million after just sixteen years of marketing the pills. 14 Though it had become an object of contempt and a symbol of quackery in England and North America by the early twentieth century, the company existed until 1989. 15 According to an 1899 Illustrated London News advertisement, Dr Williams' Pink Pills could cure a vast range of ills: anaemia, consumption, scrofula, rickets, fits, chronic erysipelas, bronchitis, lumbago, rheumatism, rheumatic gout, sciatica, eczema, paralysis, locomotor ataxy, neuralgia, St Vitus's Dance, and nervous headache.…”
Section: A Chequered Historymentioning
confidence: 99%
“…The historiographic trend towards scrutinising divisions (or lack thereof) between 'orthodox' and 'unorthodox' practitioners, and in thinking about the commercialisation of medicine through the prism of patent medicines, has generated significant work. 5 But as a trend it also suggests historians have been embedded in-perhaps even confused by-the Victorian profession's guarded attitude towards money matters. To focus upon patent medicines, devices, advertising and other of medical men's forays into explicitly commercial medicine is to draw away from explorations of the implicit role money played in all areas of medicine-including operative surgery.…”
mentioning
confidence: 99%